Gestión pública y su influencia en la regularización de la escala remunerativa del talento humano en la Comisión de Tránsito del Ecuador - Delgado Jaramillo, Silvana Carolina (2021)
This case study has been evidenced in a public institution attached to the Ministry of Transportation and Public Works of the Republic of Ecuador, legally called since the year two thousand thirteen with the name of the Ecuadorian Transit Commission known by its acronym CTE, denoting institutional presence at the national level from the transition stage of the old Guayas Transit Commission known by the acronym CTG whose institutional presence originated at the provincial level. Considering a more efficient organizational structure, divided into levels by processes according to the purposes of institutional creation, the Organic Statute by Processes in force to date is created. The fundamental objective of this research work is based on identifying the internal and external factors of public management that affect the stages of the process carried out by the Human Talent Administration Directorate, the competent area for this particular case, to influence the regularization of the remuneration scale of human resources that has not been homologated since the institutional transition. For the investigative effect, the inductive and deductive methods have been applied, since it complies with the consequent phases that allow to determine a more concrete analysis and thus, contribute favorably with a viable alternative solution, from the external point of view as an author, who practiced as an official of the institution in 2019 for seven months, knowing that to date this case has not been solved and I have considered presenting an optional result from an intellectual basis.